The Egosyntonic Nature of Anorexia: An Impediment to Recovery in Anorexia Nervosa Treatment - Gregertsen, Eva C.; Mandy, William; Serpell, Lucy (Frontiers in Psychology, 2017)
A serious problem faced by clinicians treating anorexia nervosa is the egosyntonic nature of the illness, wherein individuals with anorexia nervosa value their disorder, thereby hindering recovery for motivation and engagement with treatment. The objective of this review article is to elucidate the nature of egosyntonicity in anorexia nervosa, reviewing both qualitative and quantitative research pertaining to this topic, and, importantly, to present methods to overcome this impediment to recovery in anorexia nervosa treatment. The authors elucidate functions of anorexia nervosa for patients, both within psychological and social spheres, as well as highlight the detrimental effect of egosyntonicity in terms of illness severity and motivation for recovery. The final part of the paper contains suggestions as to methods of bypassing pitfalls linked with the influence of the egosyntonic nature of anorexia nervosa within a treatment setting, as well as an examination of three current treatments (enhanced cognitive-behavioural therapy for eating disorders, Maudsley Model of Anorexia Nervosa Treatment for Adults, and Specialist Supportive Clinical Management) in terms of the degree to which they target egosyntonicity.